(3JdNjU GdCbhGd aj JMbjb CMhGd GdQLGd (B( (3GdTjYI (B)s - (3GdejQRG eMeO GdGSJQHGPj , eMeO Hf Ydj Hf EHQGgje GdaGQSj,J (B1028 (3g` s ((3GHf NUQ Jbdi s)
(3ChdgG (B:s
(3GdMeO ddg hSdGe Ydi YHGOg GdPjf GUWai EdN s
(3BNQgG (B:s
(3aQZ efg eDdag GdQGLi Yah QHg GdgGOi GdegJOi eMeO Hf Ydi , YGTQ LeGOi GdBNQ SfI (B988 s
(3eQJH Ydi MQha GdeYLes
(3hGdejcQhajde Hg Jda HSjWs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B293 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B298s
Keywords: (3GdJGQjNs